Characterising pulverised fuel ignition in a visual drop tube furnace by use of a high-speed imaging technique - Sarroza, Archi C.; Bennet, Tom D.; Eastwick, Carol; Liu, Hao (Elsevier, 2016)
This study investigates the ignition characteristics of pulverised coal, biomass and co-firing by use of a visual drop tube furnace (VDTF) and a high speed imaging technique. Three coals (anthracite, a bituminous coal and a lignite), four biomasses (Pine, Eucalyptus, Olive Residue and Miscanthus) and various biomass-coal mixtures were tested. With each coal, biomass or their mixture, a distinct flame was established within the VDTF through the continuous feeding of the fuel under the environment of air and at a furnace temperature of 800 °C. To observe the ignition point, a Phantom v12.1 high-speed camera was used to capture the videos of fuel combustion at 500 frames per second (FPS). A technique was developed using MATLAB's image analysis tool to automate the ignition point detection. The results of the image processing were used to statistically analyse and determine the changes to the ignition behaviour with different fuels and co-firing ratios. The results obtained with the tested coals have shown that the distance to ignition increases as the coal volatile matter content decreases, whereas the opposite trend was found for the biomass fuels. Further, the addition of biomass to the anthracite significantly reduces the distance to ignition but a much less pronounced effect on the ignition was found when biomass was co-fired with the bituminous coal or lignite. The synergistic effect on the ignition of biomass-anthracite mixture is mainly attributed to the high volatile content and the potential effects of catalysis from the alkali metals present in the biomass. The results of this study have shown that the VDTF testing coupled with the image analysis technique allows for an effective and simple method of characterising ignition behaviours of pulverised coal, biomass and their mixtures.